To Reassemble Capitalism: Economic Sociology and its "Political Unconscious" - Zhikharevich, Dmitrii; Khumaryan, David (Journal of Economic Sociology, 2021)
The article offers a commentary on the discussion of the article "Political Economy after Neoliberalism" by Fligstein and Vogel, published in the current issue of the Journal of Economic Sociology. The authors draw the attention of Russian-speaking readers to the fact that the work of American researchers not only problematizes the content of political debates in the United States, but also shapes the basic principles of economic and sociological analysis of various economic systems in their connection with regulation policies and public control. Arguments are given in favor of the fact that the article by Fligstein and Vogel is a kind of manifesto of new economic sociology, demonstrating its "political unconscious"—a number of axiomatic assumptions about the functioning of the capitalist political economy, arising from the research perspective of economic sociology and related disciplines. The structure of the argument proposed in the article includes an analysis of several theoretical and empirical directions: a discussion about the varieties of empirical models of capitalism and statements about the political nature of choice of the institutional architecture of economies, the ways of organizing relations between corporations and society, and the role of the state in the economy. The authors note that the so-called neoliberal turn in social and economic policy in recent years was partly based on the purely intellectual principle in mainstream economic theory that opposes states and markets. Studies in the field of economic sociology, history, and comparative political economy demonstrate the fallacy of this statement, offering a conceptual resource for rethinking modern capitalism.